A Description of Socio-Cultural, Economic and Unwanted Pregnancy in Adolescent Single Parent Mothers - Ina Debora Ratu Ludji; Jefrin Sambara; Fatmawati Blegur; Wanti Wanti (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Unwanted pregnancy in adolescents may have negative impacts on physical, psychological, social and spiritual condition. The physical impact could endanger the teenage mothers and even their infants. Psychological stress could trigger a trial to have an abortion which can lead to death. Other psychological effect, the teenage mothers will try to escape from responsibility or keeping to continue their pregnancies by compulsion. Meanwhile, besides, social judgement and scorn, as well as banishing made by surrounding community, the community will also reject the children with unclear parents and they are considered illegal children of adulteries (Husaeni, 2009). Based on data from the Directorate of Maternal Health, the biggest cause of teenage maternal death is bleeding as a result of premature pregnancy. The purpose of this study was to determine the socio-cultural, economic of an unwanted pregnancy in single parent of adolescent mothers. This type of research is qualitative with a phenomenological and ethnographic approach. The population and sample are pregnant women and single parent mothers (having toddlers). The sample size is 9 people. Purposive Sampling Data collection by in-depth interviews (In-depth interview) to adolescents. The research was conducted in TTU District, East Nusa Tenggara. Research Results: 100% teenage single parent mothers do not work, age 15-19 years with the average education of junior high school to senior high school. Socio-culturally, teenagers imitate city life, lack of or abandon themselves from spiritual life in the family, and having trend to try new things. Teenage pregnancies are mostly unwanted as they happened accidentally. It was due to unsafe sex which was partly triggered by feeling bored with life in dormitories, adopting city life, lack of control from parents and family when teenagers return home, low or none of sexual education, simply following others, mutual consent, forced by boyfriends, poor knowledge Lack of knowledge on reproductive health and the influence of social media causes teenagers to have sex which causes unwanted pregnancies and poor socio-economic conditions. Suggestions The importance of preventing unwanted pregnancies in adolescents in schools should be started from the elementary schools by introducing health reproduction. Promotional materials related to reproductive health should be adapted to the age and development level of adolescents. In communities, especially those with low economic status, increasing awareness and knowledge about maternal and infant health is carried out through continuous health promotion.